Household income and adolescent blood pressure in a Chinese birth cohort: "Children of 1997". (November 2015) - Kwok, Man Ki; Subramanian, S.V.; Leung, Gabriel M.; Schooling, C. Mary
Abstract: The inconsistent relation of national income with population blood pressure raises questions as to whether social comparisons of relative income at individual or neighbourhood level may be more relevant than absolute income. We examined the associations of absolute household income (income per se ), absolute neighbourhood median income (average income among geographically-proximate households), relative household income [deprivation using Yitzhaki index, or rank by position] (differences in income or rank compared with others) and relative neighbourhood income inequality [Gini coefficient] (income gap within a neighbourhood) with blood pressure z-score, prehypertension or hypertension at ∼13 years using a fixed effects multilevel linear or logistic model in a Chinese birth cohort (n = 5063, 61% of follow-up). Absolute household or neighbourhood income was not associated with adolescent blood pressure. Greater relative household income deprivation was associated with higher diastolic blood pressure (0.01 z-score per USD 128 difference in Yitzhaki index, 95% confidence interval (CI) 0.005 to 0.02), so was lower relative household income rank (−0.10, 95% CI −0.15 to −0.04), but relative neighbourhood income inequality was not, when considering each income measure separately. Such associations remained when considering all income measures together. Income measures were not associated with prehypertension or hypertension. Relative household income (greater deprivation or lower rank) were positively associated with adolescent blood pressure independent of absolute household income while absolute or relative neighbourhood income had little contribution, suggesting social comparisons at a key developmental stage could be relevant. Clarifying specific effects of socioeconomic position across the life-course could inform interventions. Highlights: Lower relative household income may raise adolescent diastolic blood pressure. Absolute household income or neighbourhood income had little role in blood pressure. Social comparisons with others may affect blood pressure beyond material resources.